Nurse‐driven early rehabilitation protocol for critically ill children. Issue 1 (30th June 2022) - Chaiyakulsil, Chanapai; Thippanate, Panitnard
Abstract: Background: Physical impairment is a major morbidity in children surviving intensive care. The main objective of this study was to evaluate the effectiveness of a nurse‐driven protocol in the early mobilization of critically ill children in terms of reduction of motor dysfunction, pediatric intensive care unit stays, and ventilator days. The secondary objective was to evaluate safety, in terms of injury, dislodgement of medical devices, and cardiorespiratory instability attributable to the intervention. Methods: The early rehabilitation intervention was initiated in July 2020. This retrospective interrupted time‐series study was divided into the pre‐implementation phase (January–June 2020) and the post‐implementation phase (July–December 2020). The motor function domain of the Functional Status Scale was used to define the motor dysfunction after pediatric intensive care unit discharge. Results: Twenty‐five children were allocated in each group. The median age of the whole cohort was 11.5 months and approximately 58% of the population was male. The baseline characteristics of both groups were not statistically significant. There was a statistically significant reduction in motor dysfunction after protocol implementation (64.0% vs 36.0%; P = 0.044) with an absolute risk reduction of 28%. The number needed to treat was 3.6 children. There were no statistically significant differences in the median ventilator days, length of stay in the intensive care unit, and hospital length of stay. No complications were found. Conclusions: A nurse‐driven protocol for the early mobilization of critically ill children was feasible and could be effective in reducing post‐intensive care motor dysfunction.